Geophysical survey of earthen dam using the electrical prospecting methods - AKHMETOV, Yermek M.; ASSEMOV, Kambar M.; SHAYTOROV, Victor N. (Contributions to Geophysics and Geodesy, 2020)
The hydraulic structures for the land reclamation needs and their operation are the objects of careful attention. The water-bearing earth dams of small height pose an extra danger, where the accident occurs the most often. Such facilities should be constantly monitored to prevent the dangerous incidents. The article discusses an alternative method for studying the filtration properties of earth dams by the electrical parameters – resistivity, induced polarization and self-potential. The relative polarizability was used to exclude the influence of electrical resistivity to the induced polarization data. A study of advanced technology to identify the filter zones was carried out on an earthen dam in the Almaty region, Kazakhstan. The measurement data for three profiles are presented as the sections form in the parameters of resistivity and relative polarizability. Their complex interpretation with the respect of self-potential data, is given as a diagram of probable filtration paths. This is possibly due to the local increased watering in the dam loamy body. Then, the electric and self-potential parameters were evaluated to determine the filtering zones. The study results of above parameters have identified several water-saturated zones in the dam body. This technology could be used to estimate the condition of such objects and their engineering-geological monitoring.